2005
DOI: 10.1007/s10620-005-3012-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Helicobacter pylori on Insulin Resistance

Abstract: Helicobacter pylori causes a lifelong infection in the stomach after exposure. H. pylorihas been shown to be associated with peptic ulcer and gastric cancer development. Moreover, it is held responsible for some other nongastric diseases. Among them, coronary heart disease attracts much debate. Many studies have demonstrated a close relationship between insulin resistance and atherosclerosis. Chronic inflammation and alterations in counter-regulatory hormones are deemed responsible for the etiology of insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 34 publications
5
62
2
1
Order By: Relevance
“…Gastric bypass surgery, gluten enteropathy, some drugs and Helicobacter pylori gastritis are common causes of vitamin B12 malabsorption 1,5,16,[21][22][23][24][25][26][27][28][29] Although only 85 patients underwent endoscopic evaluation in our study, Helicobacter pylori positive gastritis rate was found quite frequently (77.6%), which is concordant with the findings of a previously published paper. 25 In that article, authors noted that Helicobacter pylori IgG values were not statistically different between the patients with low and normal vitamin B12 levels, although they were slightly higher in low B12 group. In some studies, Helicobacter pylori posivity rates were found between 50%-90% in general Turkish population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Gastric bypass surgery, gluten enteropathy, some drugs and Helicobacter pylori gastritis are common causes of vitamin B12 malabsorption 1,5,16,[21][22][23][24][25][26][27][28][29] Although only 85 patients underwent endoscopic evaluation in our study, Helicobacter pylori positive gastritis rate was found quite frequently (77.6%), which is concordant with the findings of a previously published paper. 25 In that article, authors noted that Helicobacter pylori IgG values were not statistically different between the patients with low and normal vitamin B12 levels, although they were slightly higher in low B12 group. In some studies, Helicobacter pylori posivity rates were found between 50%-90% in general Turkish population.…”
Section: Discussionsupporting
confidence: 91%
“…The most common reason accounting for deficiency is inadequate intake. [1][2][3][4][5]9,11,12,15,[20][21][22][23][24][25][26][27][28][29] Our study also displays the importance of inadequate intake of Vit B12-rich food items in the occurence of serum Vit B12 deficiency. As well known, dietary deficiency is most commonly observed among strict vegetarians, alcoholics and elderly.…”
Section: Discussionmentioning
confidence: 77%
“…HPI has been reported to promote insulin resistance by inducing chronic inflammation and affecting insulin-regulating gastrointestinal hormones (Aydemir et al 2005), whilst insulin resistance is a key element in NAFLD occurrence (Yoo et al 2013;Gunji et al 2009;Park et al 2010). Moreover, HPI could induce local infiltration of lymphocytes and granulocytes by releasing inflammatory factors such as IL-6, IL-1, and TNF-α, which induces inflammation and aggravates liver damage (Polyzos et al 2013;Park et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori might be responsible for changes in counter-regulatory hormones [12]. Therefore, as some previous studies showed, there may be a relation between H. pylori infection and insulin resistance [13]. The aim of this study was to determine the impact of H. pylori seropositivity as a risk factor for insulin resistance.…”
Section: Introductionmentioning
confidence: 94%